A computational study on gas–liquid flow in a lime slurry pond equipped with a rotary jet mixing system. (February 2017) - Qu, Yanpeng; Zhou, Cheng; Zhong, Yunpan; Chen, Songying; Wang, Ruiyan
The flue-gas desulfurization model was studied through computational fluid dynamics software. The oxidation air was asymmetrically pumped into the slurry pond. A rotary jet mixing system was established at the bottom center of the pond to agitate the lime slurry. The Navier–Stokes equation as the control equation, the standard k–ε turbulence model, sliding grids structure, and three-dimensional Eulerian multiphase flow of lime slurry were used for the numerical simulation. The independence of the meshes and the time step was verified. The distribution of the concentration of oxidation air and influents on the velocity of flow was analyzed with five angular velocities (0.01, 0.10, 0.20, 0.50, and 1 rad/s) for the rotary jet mixing. The simulation results showed that the angular velocity has a great influence on the velocity of the slurry and the distribution of the oxidation air.